Jacobsen syndrome associated with Shone’s complex: a case report - Andressa Brum; Larissa Valéria Laskoski; Fabiana Gonçalves de Oliveira Azevedo Matos; Luciana Paula Grégio d’Arce (Revista Paulista de Pediatria)
ABSTRACT Objective: The aim of this study was to report the case of a child with Jacobsen syndrome in order to provide phenotypic information about this rare genetic disorder. Case description: A 5-year-old female preschooler was diagnosed with Jacobsen syndrome by karyotype testing. She presented with a variety of craniofacial anomalies and malformations, including cardiac impairment, characterized by a cluster of malformations in the left ventricle in line with the diagnosis of Shone’s complex. Comments: Jacobsen syndrome occurs due to a deletion of contiguous genes on the long arm of chromosome 11 (11q). The main characteristics associated with this genetic disorder are short stature and delayed neuropsychomotor development, trigonocephaly and craniofacial dysmorphism, hematological alterations, and cardiac malformations, among others. Thus, the child is being monitored at a Craniofacial Anomalies Center with a multi-professional team in order to monitor her development and treat the associated comorbidities.